2022
DOI: 10.1029/2021pa004358
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing Terrestrial Paleoclimates: A Comparison of the Co‐Existence Approach, Bayesian and Probability Reconstruction Techniques Using the UK Neogene

Abstract: Little is known about the development of the modern oceanic climate regime of northwest Europe in deep time. During the Neogene (23.03-2.588 Ma), the British Isles had a unique location on the northwest edge of the Eurasian continent forming a peninsula separating the Atlantic Ocean from the North Sea (Harzhauser & Piller, 2007). Neogene sediments of the UK are therefore ideal for understanding the development of Neogene oceanic climates.The modern European climate experiences a prevalence of the westerlies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 88 publications
0
17
0
Order By: Relevance
“…However, this cooling is not recorded in the mid-latitudes of the North Atlantic region, where temperature gradients appear flat and indicate the presence of the warm oceanic current (Super et al, 2020). This warm current was likely responsible for the relatively warm temperatures observed in terrestrial palaeobotanical sites in western Europe (Utescher et al, 2015;Gibson et al, 2022;McCoy et al, in review). Evidence for Miocene biodiversity, climate, and environments in the United Kingdom (UK) are limited to isolated and poorly dated deposits, of which the Brassington Formation of central England is the most extensive and best dated (Walsh et al, 1987, Wang et al, 2018Pound et al, 2012b;Pound and Riding, 2016).…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…However, this cooling is not recorded in the mid-latitudes of the North Atlantic region, where temperature gradients appear flat and indicate the presence of the warm oceanic current (Super et al, 2020). This warm current was likely responsible for the relatively warm temperatures observed in terrestrial palaeobotanical sites in western Europe (Utescher et al, 2015;Gibson et al, 2022;McCoy et al, in review). Evidence for Miocene biodiversity, climate, and environments in the United Kingdom (UK) are limited to isolated and poorly dated deposits, of which the Brassington Formation of central England is the most extensive and best dated (Walsh et al, 1987, Wang et al, 2018Pound et al, 2012b;Pound and Riding, 2016).…”
Section: Introductionmentioning
confidence: 97%
“…Both studies proposed higher than modern Mean Annual Precipitation (MAP) of 1096-1562 mm (Pound and Riding, 2016) and 955 mm ± 150 mm (Gibson et al, 2022). However, Pound and Riding (2016) proposed a degree of precipitation seasonality in the Serravallian of the United Kingdom, whereas Gibson et al (2022) reconstructed a low degree of seasonality. Recent research has provided the first evidence of fossil fungal remains (Pound et al, 2019), and continued study revealed an abundant and diverse fungal assemblage.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations